Effect of Heavy Metals on the Germination of Wheat Seeds: Enzymatic Assay - Olga PINTILIE; Marius ZAHARIA; Adelina COSMA; Alina BUTNARU; Manuela MURARIU; Gabi DROCHIOIU; Ion SANDU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2016)
Stress caused by heavy metals is a major problem which affects agricultural productivity and, implicitly, human health. Natural flora presents differences of tolerance to heavy metals. Some plants grow well in a soil enriched with heavy metals, while others cannot develop in such conditions. This study investigates the effect of heavy metals on plant viability at molecular level and draws attention to the danger of the widespread use of toxic compounds.